The Leadership Dilemma in Modern Democracy - Ruscio, Kenneth P (Erdward Elger, 2004)
In one of the first attempts to link the expanding field of leadership studies with classic works in political theory, Kenneth Ruscio places the study of political leadership squarely within the field of democratic thought and argues that claims about the legitimate duties and responsibilities of leaders depend upon claims about principles of democracy. It is impossible to imagine effective democracies without effective leaders. Yet leaders are often seen as the problem democratic governance is designed to solve, not the solution. Through a careful but lively critique of some of the classic works in modern democratic thought - from Machiavelli to Locke and from The Federalist Papers to Rawls - The Leadership Dilemma in Modern Democracy explains what is meant by effective political leadership in a system and culture of government where the power and discretion of leaders are severely limited. A compelling and provocative study, this volume will be of interest to scholars of leadership studies, political scientists, democratic theorists, and all those interested in concepts of democracy and the challenges faced by leaders.